2022
DOI: 10.1038/s41541-021-00426-0
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy of an inactivated Zika vaccine against virus infection during pregnancy in mice and marmosets

Abstract: Zika virus (ZIKV) is a mosquito-borne arbovirus that can cause severe congenital birth defects. The utmost goal of ZIKV vaccines is to prevent both maternal-fetal infection and congenital Zika syndrome. A Zika purified inactivated virus (ZPIV) was previously shown to be protective in non-pregnant mice and rhesus macaques. In this study, we further examined the efficacy of ZPIV against ZIKV infection during pregnancy in immunocompetent C57BL6 mice and common marmoset monkeys (Callithrix jacchus). We showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 43 publications
4
17
0
Order By: Relevance
“…A previous study conducted on the conferred maternal-fetal immune protection in mice against the Zika virus upon receipt of adenovirus vector-based vaccines concluded that adenovirus vaccines offer robust protection against the Zika virus in pregnant mice. The vaccine-elicited antibodies provide neonatal protection as well [ 31 , 35 ]. Although this study does not serve as a human vaccination precedent, it is still an important conclusion in identifying the potential benefits of adenovirus vaccinations against COVID-19 in pregnant women.…”
Section: Precedent For Covid-19 Vaccination In Pregnancymentioning
confidence: 99%
“…A previous study conducted on the conferred maternal-fetal immune protection in mice against the Zika virus upon receipt of adenovirus vector-based vaccines concluded that adenovirus vaccines offer robust protection against the Zika virus in pregnant mice. The vaccine-elicited antibodies provide neonatal protection as well [ 31 , 35 ]. Although this study does not serve as a human vaccination precedent, it is still an important conclusion in identifying the potential benefits of adenovirus vaccinations against COVID-19 in pregnant women.…”
Section: Precedent For Covid-19 Vaccination In Pregnancymentioning
confidence: 99%
“…The PCR conditions were optimized using 1 μg of total RNA per reaction. Viral RNA copies were interpolated against standard curves prepared by diluting RNA from uninfected tissue spiked with a known copy number of ZIKV genomic RNA (NR-50244) obtained from BEI Resources (Manassas, VA) as described previously ( 51 ). As described previously ( 47 ), the limit of detection was defined as the cycle of threshold ( C t ) equal to 37, and the limit of quantitation was defined as a C t value of ≤35 with 100% positivity of PCR runs.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in mice, there was a positive correlation between fetal protection and the presence of neutralizing antibodies. Additionally, in marmoset monkeys, this vaccine was effective at preventing the vertical transmission of ZIKV (Kim et al 2022 ). Han et al tested the immunogenicity and safety of the TAK-426 vaccine in healthy people who were either flavivirus naive or flavivirus primed.…”
Section: Inactivated Vaccinesmentioning
confidence: 99%